Prospective longitudinal study of the pregnancy DNA methylome: the US Pregnancy, Race, Environment, Genes (PREG) study. Issue 5 (9th May 2018) - Lapato, Dana M; Moyer, Sara; Olivares, Emily; Amstadter, Ananda B; Kinser, Patricia A; Latendresse, Shawn J; Jackson-Cook, Colleen; Roberson-Nay, Roxann; Strauss, Jerome F; York, Timothy P
Abstract : Purpose: The goal of the Pregnancy, Race, Environment, Genes study was to understand how social and environmental determinants of health (SEDH), pregnancy-specific environments (PSE) and biological processes influence the timing of birth and account for the racial disparity in preterm birth. The study followed a racially diverse longitudinal cohort throughout pregnancy and included repeated measures of PSE and DNA methylation (DNAm) over the course of gestation and up to 1 year into the postpartum period. Participants: All women were between 18 and 40 years of age with singleton pregnancies and no diagnosis of diabetes or indication of assisted reproductive technology. Both mother and father had to self-identify as either African-American (AA) or European-American (EA). Maternal peripheral blood samples along with self-report questionnaires measuring SEDH and PSE factors were collected at four pregnancy visits, and umbilical cord blood was obtained at birth. A subset of participants returned for two additional postpartum visits, during which additional questionnaires and maternal blood samples were collected. The pregnancy and postpartum extension included n=240 (AA=126; EA=114) and n=104 (AA=50; EA=54), respectively. Findings to date: One hundred seventy-seven women (AA=89, EA=88) met full inclusion criteria out of a total of 240 who were initially enrolled. Of the 63 participants who met exclusion criteria after enrolment, 44 (69.8%) were associated with a medical reason. Mean gestational age at birth was significantly shorter for the AA participants by 5.1 days (M=272.5 (SD=10.5) days vs M=277.6 (SD=8.3)). Future plans: Future studies will focus on identifying key environmental factors that influence DNAm change across pregnancy and account for racial differences in preterm birth.